Multilingualism In Indonesia: An Introduction To Makassarese Language - Wongso Adi Saputra (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
Indonesia is a country which has more than 652 local languages besides Bahasa Indonesia (BI) as a national language which is used as an Intranational Lingua Franca (ILF). Hence, it is very common for Indonesian people to be multilingual humans. Some of the local languages used in Indonesia are; Java, Sunda, Bugis, Makassarese, and etc.  Makassarese is one of local language that is used in some area in South Sulawesi island including Makassar city. This research is a corpus analysis data research. The data taken are from researcher experiences and the publish and unpublish document in Makassarese. Furthermore, the researcher uses sentence glossing, and describes the comparison of Makasarese with Indonesian and English. As the result, the description of Makassarese is elaborated based on consonant in sentence, reduplication in suffix, perfective/imperfective aspects, and alignment of verbal sentence marking.